Global synergistic actions to improve brain health for human development - Owolabi, Mayowa O; Leonardi, Matilde; Bassetti, Claudio; Jaarsma, Joke; Hawrot, Tadeusz; Makanjuola, Akintomiwa I; Dhamija, Rajinder K; Feng, Wuwei; Straub, Volker; Camaradou, Jennifer; Dodick, David W; Sunna, Rosita; et al. (Nature reviews. Neurology, 2023)
The global burden of neurological disorders is substantial and increasing, especially in low-resource settings. The current increased global interest in brain health and its impact on population wellbeing and economic growth, highlighted in the World Health Organization's new Intersectoral Global Action Plan on Epilepsy and other Neurological Disorders 2022-2031, presents an opportunity to rethink the delivery of neurological services. In this Perspective, we highlight the global burden of neurological disorders and propose pragmatic solutions to enhance neurological health, with an emphasis on building global synergies and fostering a 'neurological revolution' across four key pillars - surveillance, prevention, acute care and rehabilitation - termed the neurological quadrangle. Innovative strategies for achieving this transformation include the recognition and promotion of holistic, spiritual and planetary health. These strategies can be deployed through co-design and co-implementation to create equitable and inclusive access to services for the promotion, protection and recovery of neurological health in all human populations across the life course.
Keywords: cíle; trvale udržitelný rozvoj; Světová zdravotnická organizace; Sustainable Development; Brain; World Health Organization; mezinárodní spolupráce; Biomedical Research; Mental Health; spiritualismus; Spiritualism; celosvětové zdraví; duševní zdraví; environmentální politika; Nervous System Diseases; nemoci nervového systému; Goals; Global Health; Stakeholder Participation; biomedicínský výzkum; lidé; Humans; účast zainteresovaných stran; Neurology; mozek; Holistic Health; holistické zdraví; neurologie; International Cooperation; Environmental Policy